Sistem Peradilan Pidana Berkeadilan melalui Pendekatan Kontrol dalam Proses Penegakan Hukum - Hasuri Hasuri (Ajudikasi : Jurnal Ilmu Hukum, 2019)
Justice in the criminal justice system is a static and dynamic in accordance with the space, time and conditions of criminal acts, justice has legal aspects in criminal justice. Understanding justice in the criminal justice system will be found differences in justice that are relatively in accordance with criminal acts and the consequences of these criminal acts. The clean and authoritative administration of justice is the ideals of the judiciary in Indonesia and the hope of seeking justice, the face of the judiciary forms a fair criminal justice system if under ideal conditions, sometimes the criminal justice system does not escape the pressures of the interests of those who want to polarize the law in accordance with a sense of justice constructed by law enforcement as a sub-system of the judiciary body. Normative law enforcement is a series of actions to maintain material law that has been violated by legal subjects in general, law enforcement in the criminal justice system has unique characteristics and procedures in accordance with the legal system adopted and continuously shifts in balance through a renewed legal system . Relevant issues to be examined are: What is the basic idea of a fair trial, How to approach the control of the criminal justice system as an alternative to distributing justice. This study uses a constructivist paradigm with Non-Doctrinal Approach Method or socio-legal research with Qualitative methods, the research specifications are using analytical descriptive, the main data types in this study are field data and are supported by library data, data analysis methods are using Juridical-Qualitative data. For field data validation using interview and observation techniques. The results of the research and discussion in this study are in accordance with the problems that were the focus of the study found the following matters: First, the lack of harmony between the legal system and the criminal law enforcement system has an impact on the basic idea of the criminal justice system. Second, control in the criminal justice system is part of the transformation and reform of the legal system in the criminal justice system.